BIFURKASI DARI HASIL MODIFIKASI SISTEM PERSAMAAN LORENZ - Faisal Faisal (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2012)
The Lorenz equation system is the family of Chen's system of equations and systems equation Lu. The system of equations of Lorenz, the system of Chen equations and the system of equations Lu they have three positive parameters. Differences modify the system of equations of Lorenz with the three systems of equations which (Lorenz equation system, Chen equation system, Lu equation system) respectively lies in the second equation. Modification of the system of equations Lorenz has two parameters with one parameter may be negative. In this paper will be analyzed whether or not there is bifurcation. The results of this paper shows the system having subcritical Hopf bifurcation.